Conduta no tratamento de gengivite ulcerativa necrosante (GUN) em serviço de urgência - Steffens, João Paulo [UNESP]; Coimbra, Leila Santana [UNESP]; Marcantonio, Rosemary Adriana Chierici [UNESP]; Spolidório, Luis Carlos [UNESP] (My University, 2011)
Necrotizing ulcerative gingivitis is a periodontal disease which suddenly appears and presents an acute clinical course, characterized by patients' pain, discomfort and halitosis. Ulceration on papilla and marginal gingiva can be observed. For this reason, patients presenting this condition may seek dental assistance in Health Units or Graduation Institutions, being the dentist responsible for the adoption of a clinical treatment that minimizes symptomatology. The purpose of this case report is to expose and discuss aspects of clinical treatment for this disease applied to the reality of this service.

A gengivite ulcerativa necrosante é uma doença periodontal que apresenta curso clínico agudo, de início rápido, caracterizada por dor, desconforto e mau hálito do paciente, sendo observadas ulcerações na papila interdental e gengiva marginal. Por este motivo, os pacientes com esta condição podem buscar serviços de urgência odontológica em Unidades de Saúde ou Instituições de Ensino, cabendo ao cirurgião-dentista/plantonista adotar a conduta clínica adequada para minimizar a sintomatologia. O objetivo deste relato de caso clínico foi expor e discutir alguns aspectos da conduta de tratamento desta enfermidade aplicados à realidade deste serviço.
Treatment for necrotizing ulcerative gingivitis (NUG) in an urgency service - a case report
Keywords: Gingivitis; Necrotizing ulcerative; Health services; Periodontics/methods; Gengivite ulcerativa necrosante; Serviços de saúde; Periodontia/métodos